Expression of extracellular matrix components and related growth factors in human tendon and muscle after acute exercise. Issue 3 (23rd November 2011) - Heinemeier, K. M.; Bjerrum, S. S.; Schjerling, P.; Kjaer, M.
Abstract : Acute kicking exercise induces collagen synthesis in both tendon and muscle in humans, but it is not known if this relates to increased collagen transcription and if other matrix genes are regulated. Young men performed 1 h of one‐leg kicking at 67% of max workload. Biopsies were taken from the patellar tendon and vastus lateralis muscle of each leg at 2 ( n = 10), 6 ( n = 11), or 26 h ( n = 10) after exercise. Levels of messenger ribonucleic acid mRNA for collagens, noncollagenous matrix proteins, and growth factors were measured with real‐time reverse transcription polymerase chain reaction. In tendon, gene expression was unchanged except for a decrease in insulin‐like growth factor‐IEa (IGF‐IEa; P < 0.05). In muscle, collagen expression was not significantly altered, while levels of connective tissue growth factor (CTGF), IGF‐IEa, transforming growth factor‐β1, ‐2 (TGF‐β), and the TGF‐β receptor II mRNA were increased ( P < 0.05). Matrix components tenascin‐C, fibronectin, and decorin were also induced in loaded muscle ( P < 0.05), while fibromodulin was unaffected. In conclusion, the relatively robust changes in matrix components and related growth factors in muscle indicate a stimulation of extracellular matrix even with moderate exercise. However, in tendon tissue, this exercise model does not appear to induce any anabolic response on the transcriptional level.